Outsiders and bystanders in Erik Skjoldbjærg's The Pyromaniac (2016). Issue 2 (2nd April 2018) - Gjelsvik, Anne
ABSTRACT: This article discusses the Norwegian film The Pyromaniac (Erik Skjoldbjærg 2016) as an artistic attempt to come to terms with terrorism, and as a cinematic treatment of the Norwegian terror attacks of 22nd of July 2011. The film is discussed in relation with several written accounts on 22nd of July and focus is on the role of the individual, the family and the society when it comes to guilt and shame following incomprehensible events.